About antiviral effects of vitamin D - O. A. Gromova; I. Yu. Torshin; D. E. Frolova; N. P. Lapochkina; O. A. Limanova (Медицинский совет, 2020)
Preventing infectious diseases is very important in obstetric and gynaecological practice. Vitamin D is a complex regulator of innate and adaptive immunity. It is known that lack of vitamin D reduces antibacterial and antiviral immunity, stimulates the development of pathologies associated with chronic systemic inflammation. Evidence from evidence-based medicine indicates the importance of using vitamin D preparations to support immunity. The results of fundamental and clinical studies have shown that chronic inflammation and congenital immunity disorders resulting from vitamin D deficiency significantly reduce the body’s resistance not only to tuberculosis, but also to viral hepatitis, acute respiratory infections, papillomavirus and herpesvirus. In addition to a pronounced antibacterial effect, vitamin D is also characterized by its antiviral action. By increasing the expression of interferon-alpha, cathecidine, defensin and antiviral microRNA, vitamin D activates various mechanisms of congenital antiviral immunity. Studies show the need to compensate for vitamin D deficiency for successful therapy of viral hepatitis, respiratory infections, human papillomavirus (HPV) and herpesvirus. In the present article the molecular fundamentals of antiviral action of vitamin D are sequentially considered, as well as the results of fundamental and clinical studies indicating the action of vitamin D against the viruses of hepatitis, herpes, RSV, Epstein-Barr, human papillomavirus, the possibility of using vitamin D in the treatment of these and other viral pathologies is considered. The authors analyzed data on the effect of vitamin D on immunity functions and antiviral protection of the human body.